Growth inhibition of cultured cancer cells by Ribes nigrum leaf extract - Mikayel Ginovyan; Agnieszka Bartoszek; Izabela Koss-Mikołajczyk; Barbara Kusznierewicz; Pierre Andreoletti; Mustapha Cherkaoui-Malki; Naira Sahakyan (AIMS Biophysics, 2022)
The present article includes data on the possible selective cytotoxic effect of extract of Ribes nigrum L. growing at high Armenian landscape. For this purpose, different non-cancer (microglial BV-2 wild type (Wt), acyl-CoA oxidase 1 (ACOX1) deficient (Acox1−/−) and cancer (human colon adenocarcinoma HT29 and human breast cancer MCF7) cell lines were applied. R. nigrum leaf ethanol extract showed a growth inhibition effect towards HT29 and MCF7 cells started from 6 h of treatment at the concentration of 0.5 mg/mL DW. The lowest concentration (0.125 mg/mL DW) of the investigated extract expressed cytotoxicity after 72 hours following cancer cell treatment. In contrast to the cancer cells, in the case of the tested non-cancer cells, cytotoxic effect was not observed at the applied concentrations. The extract sub-cytotoxic concentration, in this case, was reported to be the 1 mg/mL DW. Further investigations are needed to confirm the selective cytotoxicity and possible action mechanisms of the leaf extract of R. nigrum.